Modelling a hydrologic Black-Box - Stella, Juan M.; Warner, Glenn S. (Tecnología y ciencias del agua, 2018)
Stella, J. M., & Warner, G. S. (January-February, 2018). Modelling a hydrologic Black-Box. Water Technology and Sciences (in Spanish), 9(1), 101-112, DOI: 10.24850/j-tyca-2018-01-07.Â Â Hydrologic simulation models have become an essential tool in the modern world of water management; they are used extensively and play an important auxiliary role in fulfilling the core tasks of water management, in policy preparation, operational water management and research. A physical based hydrologic Black-Box model was created to simulate the water inflows and outflows of the system that could be used for an educational purpose. Then a mathematical model using StellaÂ® software was created to simulate the Black-Box model. The results of the simulations show that the combination of a physical hydrologic Black-Box model and the mathematical model using the StellaÂ® software can helps students understand the basic hydrologic processes.Â Â